Intra-European Student Mobility in International Higher Education Circuits : Europe on the Move - Mol, Christof Van; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Adopting an interdisciplinary approach, this book empirically investigates the (im)mobility decisions, social network formation, sense of European identity and migratory aspirations of higher education students. It draws on a large-scale survey, in-depth interviews and focus groups, conducted in Austria, Belgium, Italy, Norway, Poland and the UK.
Keywords: Science; Science, general